Political Attitudes of Urban Social Organizations during the Political Crisis in Guatemala (2015-2017) - Velásquez Pérez, Luis Guillermo (2024)
The study, employing non-parametric tests, assesses the relationships that existed among the political attitudes of urban social organizations that actively engaged during the crisis and the reformist agenda promoted by anti-corruption institutions in Guatemala. It was determined that these relationships are heterogeneous, and that at least one of the reasons for advocating the resignation of President Otto Pérez Molina was significantly distinct. Furthermore, the stances taken regarding the 2015 elections were found to be independent of those assumed for the reform of electoral law and political parties. Additionally, it was observed that at least one of the distributions of evaluations pertaining to legal reforms approved between 2015 and 2016 differed significantly.